2009
DOI: 10.1038/hr.2009.47
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol attenuates angiotensin II-induced interleukin-6 expression and perivascular fibrosis

Abstract: Recent studies have shown that resveratrol (3,5,4¢-trihydroxystilbene), a polyphenolic compound found in grapes and red wine, has various beneficial effects on cardiovascular diseases and prolongs the life span of mice fed a high-fat diet. We hypothesized that resveratrol may attenuate vascular inflammatory response induced by angiotensin (Ang) II. We examined the effect of resveratrol on Ang II-induced interleukin (IL)-6 expression in vascular smooth muscle cells (VSMCs). Resveratrol significantly attenuated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 41 publications
1
27
1
Order By: Relevance
“…The present findings show a beneficial role for Sirt1 in protecting the kidney from fibrosis, which supports previous studies showing an antifibrotic effect of resveratrol (51)(52)(53). Although the detailed mechanisms of renal fibrosis after ureteral obstruction are still incompletely understood, fibrosis appears to be a maladaptive response to injury.…”
Section: Figuresupporting
confidence: 78%
“…The present findings show a beneficial role for Sirt1 in protecting the kidney from fibrosis, which supports previous studies showing an antifibrotic effect of resveratrol (51)(52)(53). Although the detailed mechanisms of renal fibrosis after ureteral obstruction are still incompletely understood, fibrosis appears to be a maladaptive response to injury.…”
Section: Figuresupporting
confidence: 78%
“…With regard to endothelial function, the majority of the atheroprotective activity of resveratrol was thus far believed to originate from the inhibition of pro-inflammatory signaling via suppression of NF-B activity 7,21,22) . In accordance with this, we previously demonstrated that resveratrol significantly inhibited adhesion molecule induction and monocytic cell adhesion to TNF--stimulated endothelial cells under hemodynamic conditions corresponding to these in atherosclerosis-prone arterial bifurcations 10) .…”
Section: Discussionmentioning
confidence: 99%
“…According to our previous experience 12 , the viscosity of the preparation was based on the non-ionic contrast medium iomeprol (Iomerol ® , Bracco, Italy; kinematic viscosity at 37°C: 5.617±0.034 mm 2 •s -1 ). The final kinematic viscosity of the RSV-c was very close to that of the reference solution (6.097±0.0379 mm 2 s -1 ).…”
Section: Preparation Of the Compound (Rsv-c)mentioning
confidence: 99%
“…There are several pioneering reports on RSV, including studies on the inhibition of the arachidonate metabolism via interactions with the 5-lipoxygenase and cyclooxygenase pathways in leukocytes [6][7][8][9][10][11][12] . However, RSV attracted little interest until 1979, when the "French Paradox" 13 reported the positive benefit of an RSV-containing diet, in particular the moderate consumption of red wine, for coronary heart disease.…”
Section: Introductionmentioning
confidence: 99%